Forced convective heat transfer analysis for two-dimensional slot jet of water-CuO nanofluid - Etminan, Amin; Zambri Harun, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper investigates the effect of the diameter and the volume fraction variation of the centre nanoparticles on the heat transfer characteristics of a two-dimensional slot jet. The jet impinges on stationary flat, convex, and concave aluminium plates. A forced convective heat transfer coefficient of water-CuO nanofluid impinges on a smooth plate under a constant heat flux. The finite volume method (FVM) is implemented for nanoparticles with diameters varying from 7 to 60 nanometers, volume fractions changing from 0 to 5%, and the Reynolds numbers ranging from 1800 to 2800. A grid independence study is carried out to find a grid size that predicts the results accurately and further grid refinement changes the results insignificantly. The single-phase model shows a capability to predicts the fluid and heat transfer parameters faster and make it more suitable for numerical simulations compared to the two-phase model. The results indicate a higher heat transfer coefficient of nanofluid in comparison with distilled water. As the Reynolds number and nanoparticle volume concentrations increase, the heat transfer rate increases on the surface whilst smaller nanoparticle diameters increase during the cooling process. The increase in the diameter of nanoparticles enhances the Nusselt number on the plate by up to 10%. The same geometrical details, thermophysical, and boundary conditions have been employed in all calculations for distilled water jet simulations to validate the fluid flow behaviour and heat transfer parameters with available experimental data in the literature.